Syriac Christians and Popular Religion in Early Ottoman Mesopotamia: The Testimony of Abū al-Maʿānī - Minov, Sergey (Aramaic studies, 2024)
This article presents the hitherto unpublished Syriac text of the Turgāmā on Charms and Sorcery, a specimen of pastoral literature produced by Ignatius VII ʿAzīz bar Sāḇtā, known also as Abū al-Maʿānī, who served as the patriarch of Ṭūr ʿAbdīn from 1461 to 1481. A representative of the centuries-long tradition of polemic against magic and use of amulets among Syriac Christians, the work is a rare and valuable witness to the dynamics of popular religion among West Syrians of early Ottoman Mesopotamia. The text is accompanied by an English translation and a brief discussion.